The Potential of Gamification in Developing Pre-Service Physics Teachers' Critical and Creative Thinking Skills - Saprudin, Saprudin; Liliasari, Liliasari; Prihatmanto, Ary Setijadi; Setiawan, Andhy (Program Studi Pendidikan Fisika UHAMKA, 2019)
This article is a part of the research related to the development of gamification models to improve critical and creative thinking skills of pre-service physics teachers (PPTs). This case study is a preliminary research to describe the potential of gamification in physics experiments that was involved 25 PPTs at one of the universities in Bandung. The potential of gamification was analyzed from the results of observations, and the monitoring of the physics experiment activities assisted by WhatsApp social media. Through the implementation of gamification, physics experiments can be designed like gameplay so that it was expected to motivate PPTs to be more actively involved in physics experiment activities. Besides that, the presence of gamification can create an atmosphere of physics experiments to be more enjoyable.